Factors Affecting Blockchain Adoption In Indonesia - Gaguk Dwi Prasetyo Atmoko; Dewi Tamara; David Yuwono; Sarah Fauziah (Ridwan Institute, 2021)
Two cognitive beliefs in the Technology Acceptance Model (TAM), namely perceived usefulness and perceived ease of use, have been considered central in determining acceptance of information technology in recent decades. These two cognitive beliefs are not necessarily able to fully explain user behavior towards new information technologies such as blockchain technology, so this study will explore the factors that influence the acceptance of blockchain technology in Indonesia by integrating the TAM model with aspects of perceived security, perceived risk, trust, perceived strategic value, and cost-saving to develop a comprehensive TAM. Based on a survey conducted on 250 people who work in the banking, telecommunications, and government sectors as well as the research design using quantitative, the model was tested using a structural equation modeling which resulted in empirical findings stating that there was a significant effect given by perceived security, perceived risk, trust, perceived strategic value, and cost-saving, to the acceptance of blockchain technology